SISTEM PAKAR UNTUK MENDETEKSI KERUSAKAN SISTEM OPERASI HANDPHONE BLACKBERRY BERBASIS WEB (Information Technology and Telematics, 2014)
ABSTRACT The continued development of blackberry mobile technology makes society more interest in using it. With the model of operating system and some applications in it that always changes or upgrades in order to accelerate performance blackberry technology makes society must always follow its development. This expert system will be created with the aim to help the community detecting damage - any damage as a step towards early detection of damage blackberry operating system. An expert system for detecting damage to the operating system blackberry mobile phone which can browse damage by way of testing the rules put forward reasoning techniques (forward chaining) and provide simplification solutions to the damage to the mobile operating system blackberry. The use of the method of knowledge representation used to use a rule-based representation method (rule base). Detection of damage to the operating system blackberry mobile phones carried by the user by selecting the symptoms that arise, the selection of symptoms according to the rule (the rule base) result in a damage detection results are useful for the prevention or early treatment for the damage. This system development using HTML and PHP programming languages ​​with the database MySQLdan Apache web serve Keywords: expert system, damages, blackberry, PHP, MySQL